(3caGjI GdoeMJGL def djS aj GdOjHGLs - (3CHhGdYHGS CMeO HGHG Hf CMeO Hf CMeO Hf YeQ Hf eMeO CbjJ GdJfHcJj GdJcQhQj GdShOGfj GdeGdcjs; (3GdJfHcJj , CMeO HGHG Hf CMeO Hf CMeO Hf YeQ GdJcQhQj GdShOGfj, CHh GdYHGS,J (B1036 (3g` s
(3ChdgG (B:s
(3hHYO agPG LRA ENJUQJg ef GdPjd GdPj PjdJ Hg cJGH GdOjHGL GdePgH aj eYQaI CYjGf YeGA GdePgH ddEeGe HQgGf GdOjf Hf aQMhf GdoeSei fjd GdEHJgGL HJWQjR GdOjHGL s
(3BNQgG (B:s
(3hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf HJGQjN jhe GdLeYI eSJgd UaQ YGe EKfJi YTQ hCda hUdi Gdg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG eHGQckG s
(3GfXQ Qbe (B765s
(3Qbe (B1181 (3JGQjNs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs